Medical communication, internalized “good mother” norms, and feminist self-identification as predictors of maternal burnout - Milman, Daisy; Sternadori, Miglena (Frontiers in Communication, 2024)
This survey of self-identified mothers (n = 254) investigated whether medical professionals' communications are associated with perceived maternal stress and maternal burnout in relation to the social expectations to be a "good mother." Participants who recalled discomfort-inducing medical communications that directly or indirectly referenced motherhood norms reported higher levels of internalized good-mother expectations and maternal burnout. A process model showed that the frequency of recalled medical communications, length of motherhood, and feminist self-identification moderated the relationship between the degree of internalization of good-mother expectations and maternal burnout. The findings are discussed in the context of self-discrepancy theory, concluding with practical implications for medical professionals.